TREND: Statistics Canada. CANSIM: Accommodation and Food | Province: Manitoba, New Brunswick, Northwest Territories | Table ID: 1830006 | Table: Sales of alcoholic beverages by volume, value and per capita 15 years and over, fiscal years ended March 31 | Variable: Total alcoholic beverages, Total products, Total sales, Value in dollars, 1950 - 2012. Data-Planet™ Statistical Datasets by Conquest Systems, Inc. Dataset-ID: 075-001-009Statistics Canada. CANSIM: Arts, Entertainment and Recreation | Province: Manitoba, New Brunswick, Northwest Territories | Table ID: 1830006 | Table: Sales of alcoholic beverages by volume, value and per capita 15 years and over, fiscal years ended March 31 | Variable: Total alcoholic beverages, Total products, Total sales, Value in dollars, 1950 - 2012. Data-Planet™ Statistical Datasets by Conquest Systems, Inc. Dataset-ID: 075-001-010Statistics Canada. CANSIM: General Business Consumers and Property Services Statistics | Province: Manitoba, New Brunswick, Northwest Territories | Table ID: 1830006 | Table: Sales of alcoholic beverages by volume, value and per capita 15 years and over, fiscal years ended March 31 | Variable: Total alcoholic beverages, Total products, Total sales, Value in dollars, 1950 - 2012. Data-Planet™ Statistical Datasets by Conquest Systems, Inc. Dataset-ID: 075-001-008 - Statistics Canada (Data-Planet™ Statistical Datasets by Conquest Systems, Inc., 2016)
Statistics Canada. CANSIM: Accommodation and Food | Province: Manitoba, New Brunswick, Northwest Territories | Table ID: 1830006 | Table: Sales of alcoholic beverages by volume, value and per capita 15 years and over, fiscal years ended March 31 | Variable: Total alcoholic beverages, Total products, Total sales, Value in dollars, 1950 - 2012. Data-Planet™ Statistical Datasets by Conquest Systems, Inc. Dataset-ID: 075-001-009 Dataset: Presents statistics on travel agencies and tour operators, as well as the hospitality industry (ie, hotels, motor hotels, resorts, restaurants, food service contractors, caterers, mobile food services, and drinking places) in Canada and subnational geographies as available. CANSIM is Statistics Canada's key socioeconomic database. The datasets included here provide statistics on the Canadian population, and the nation’s resources, economy, society, and culture. In addition to conducting a Census every five years, approximately 350 active surveys are conducted on virtually all aspects of Canadian life. Statistics are provided for the nation as a whole, provinces, and other subnational geographies where available. http://www5.statcan.gc.ca/cansim/ Category: Industry, Business, and Commerce, Prices, Consumption, and Cost of Living Subject: Tourism Industry, Travel Industry, Accommodations Industry Source: Statistics Canada Established as Canada's central statistical office by the Statistics Act of 1985, Statistics Canada is required to "collect, compile, analyse, abstract and publish statistical information relating to the commercial, industrial, financial, social, economic and general activities and conditions of the people of Canada." Its main objectives are to provide statistical information and analysis about Canada’s economic and social structure and to promote sound statistical standards and practices. http://www.statcan.gc.ca/Statistics Canada. CANSIM: Arts, Entertainment and Recreation | Province: Manitoba, New Brunswick, Northwest Territories | Table ID: 1830006 | Table: Sales of alcoholic beverages by volume, value and per capita 15 years and over, fiscal years ended March 31 | Variable: Total alcoholic beverages, Total products, Total sales, Value in dollars, 1950 - 2012. Data-Planet™ Statistical Datasets by Conquest Systems, Inc. Dataset-ID: 075-001-010 Dataset: Presents statistics on performers and performing arts companies (actors/actresses, singers, dancers, musical groups, artists, athletes, and other entertainers); spectator sports; golf courses and country clubs; skiing facilities; fitness and recreational sports centers; marinas; bowling centers; all other amusement and recreation industries; and heritage institutions in Canada and subnational geographies as available. CANSIM is Statistics Canada's key socioeconomic database. The datasets included here provide statistics on the Canadian population, and the nation’s resources, economy, society, and culture. In addition to conducting a Census every five years, approximately 350 active surveys are conducted on virtually all aspects of Canadian life. Statistics are provided for the nation as a whole, provinces, and other subnational geographies where available. http://www5.statcan.gc.ca/cansim/ Category: Industry, Business, and Commerce, Prices, Consumption, and Cost of Living Subject: Entertainment Industry, Entertainment Services, Recreation Services Source: Statistics Canada Established as Canada's central statistical office by the Statistics Act of 1985, Statistics Canada is required to "collect, compile, analyse, abstract and publish statistical information relating to the commercial, industrial, financial, social, economic and general activities and conditions of the people of Canada." Its main objectives are to provide statistical information and analysis about Canada’s economic and social structure and to promote sound statistical standards and practices. http://www.statcan.gc.ca/Statistics Canada. CANSIM: General Business Consumers and Property Services Statistics | Province: Manitoba, New Brunswick, Northwest Territories | Table ID: 1830006 | Table: Sales of alcoholic beverages by volume, value and per capita 15 years and over, fiscal years ended March 31 | Variable: Total alcoholic beverages, Total products, Total sales, Value in dollars, 1950 - 2012. Data-Planet™ Statistical Datasets by Conquest Systems, Inc. Dataset-ID: 075-001-008 Dataset: Presents statistics on general topics related to business, consumer, and property services in Canada. Topics cover many subtopics, or are too specific to correspond to any of the subtopics. CANSIM is Statistics Canada's key socioeconomic database. The datasets included here provide statistics on the Canadian population, and the nation’s resources, economy, society, and culture. In addition to conducting a Census every five years, approximately 350 active surveys are conducted on virtually all aspects of Canadian life. Statistics are provided for the nation as a whole, provinces, and other subnational geographies where available. http://www5.statcan.gc.ca/cansim/ Category: Industry, Business, and Commerce, Prices, Consumption, and Cost of Living Subject: Consumers, Businesses, Property Source: Statistics Canada Established as Canada's central statistical office by the Statistics Act of 1985, Statistics Canada is required to "collect, compile, analyse, abstract and publish statistical information relating to the commercial, industrial, financial, social, economic and general activities and conditions of the people of Canada." Its main objectives are to provide statistical information and analysis about Canada’s economic and social structure and to promote sound statistical standards and practices. http://www.statcan.gc.ca/